A Simple and Green Analytical Method for the Determination of Formaldehyde - Gasparini, Fabricia [UNESP]; Weinert, Patricia L. [UNESP]; Lima, Liliane S. [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Soc Brasileira Quimica, 2008)
A green spectrophotometric analytical method for determination of formaldehyde in commercial samples was designed and investigated. Replacement of hazardous reagents was explored to attain the clean chemistry standards. The method is based on formaldehyde reaction with chromotropic acid in the presence of magnesium sulphate producing a stable complex Mg(2+)/cyclotetrachromotropylene (lambda(max) = 535 nm). To the best of our knowledge, there are no reports on the use of the above mentioned reaction for this determination. The experimental conditions were optimized by the response surface methodologies. Beer's Law is obeyed in a concentration range of 3 to 11 mg L(-1) of formaldehyde with a correlation coefficient of 0.999. The proposed method was applied for the determination of formaldehyde in commercial disinfectants and deffrizing hair products. The results were favorably compared with those of the official method, with good accuracy and precision.
Keywords: formaldehyde; Mg(2+)/cyclotetrachromotropylene; disinfectants; deffrizing products; green analytical chemistry